2022
DOI: 10.1128/spectrum.02817-22
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisCell-to-Cell Spread through Tunneling Nanotubes

Abstract: Intracellular bacterial pathogens often undergo a life cycle in which they parasitize infected host cells in membranous vacuoles. Two pathways have been described by which chlamydia can exit infected host cells: lytic cell destruction or exit via extrusion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…Intrigued by the induction of the formation of these B cell protrusions by the parasite, we set out to investigate whether these amastigote-induced protrusions could serve any functional purpose. Previous studies have demonstrated TNTs and TNT-like protrusions formed by other cell types to be exploited for disease propagation by bacteria ( 21 23 ) and viruses ( 24 26 ), so we wanted to know whether these protrusions could be used by L. donovani to pass between cells and hence propagate activation. Indeed, we frequently observed the presence of L. donovani amastigotes on the protrusions formed between two B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrigued by the induction of the formation of these B cell protrusions by the parasite, we set out to investigate whether these amastigote-induced protrusions could serve any functional purpose. Previous studies have demonstrated TNTs and TNT-like protrusions formed by other cell types to be exploited for disease propagation by bacteria ( 21 23 ) and viruses ( 24 26 ), so we wanted to know whether these protrusions could be used by L. donovani to pass between cells and hence propagate activation. Indeed, we frequently observed the presence of L. donovani amastigotes on the protrusions formed between two B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These B cell TNTs were shown to enable the transport of plasma membrane proteins on the outside of the tubules as well as to allow passage of microvesicles through the inside of the tubules ( 39 , 41 ). In other cell types, previous studies have demonstrated these tubules to be exploited for disease propagation by bacteria, including Listeria monocytogenes ( 21 ), Mycobacterium bovis ( 22 ), and Chlamydia trachomatis ( 23 ), and viruses, such as HIV-1 ( 24 ), influenza A virus ( 25 ), and SARS-CoV-2 ( 26 ). Thus, the involvement of these TNT-like protrusions in the dissemination of L. donovani among B cells represents the first report of this mechanism of intercellular communication in the context of a parasitic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to viruses, previous work has shown that C.t. may spread cell-to-cell by nanotubules 69 . Thus, it is conceivable that effector proteins may also be transmitted to adjacent cells via this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It interferes with the antigen-presenting function of antigen-presenting cells (APCs) (downregulation of MHC class I and II molecules) ( 54 , 55 ), regulating specific cytokines with multiple effects (IL-18, IFN-γ, TNF-α), and anti-apoptosis (increased cell survival signaling and CPAF release) ( 56 58 ). In addition, recent studies have shown that intracellular RBs can enter uninfected neighboring cells via tunneling nanotubes (TNT) ( 59 ). This allows Chlamydia to remain unexposed to body fluids, thus evading to some extent the pursuit of various cytokines in body fluids.…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%